Voice, Language, and Storytelling: The Craft of Narrative Experimentation in John Edgar Wideman’s Fiction - AZON, Sènakpon Adelphe Fortuné (My University, 2018)
The self-assertion of marginalized people has always been made in a conscious distantiation from the cultural values of the mainstream. Self-assertion usually finds its way in literature through cultural memory, language valuation, and voice. John Edgar Wideman is one of the African American authors whose literary esthetics is radically committed to African American’s social and cultural redemption. His work, produced from the margins of the American society, is a forceful assertion of identity that intertwines and fuses. West African cultural strands, orality, popular arts, audiovisual arts techniques, and various English language registers, in a borderline politics of experimentation. This paper purports to bring out, through a reading based on narratology, postcolonialism, and postmodernism, that expression of the politics of identity in Wideman’s aesthetics of experimentation. L'affirmation de soi, chez les peuples marginalisés, a toujours été faite dans une distanciation consciente vis-à-vis des valeurs de la culture dominante. En littérature, elle trouve habituellement son moyen d’expression dans la mémoire culturelle, la langue et la voix. John Edgar Wideman est l'un des auteurs afro-américains qui on tune esthétique littéraire radicalement engagéepourla rédemption sociale et culturelle des Afro-américains. Son oeuvre, issue des marges de la société américaine, est une affirmation vigoureuse de l'identité noire qui mêle et fusionne courants culturels ouestafricains, arts populaires, techniques artistiques audiovisuelles et divers registres de la langue anglaise, dans une politique radicaled' expérimentation. Cet article a pour objectif de faire ressortir, à travers une lecture basée sur la narratologie, le post-colonialisme et le postmodernisme, cette expression de la politique de l'identité dans l'esthétique expérimentale de Wideman.
Keywords: Cultural Memory; African American; Narrative; Voice - Marginalization - Mémoire Culturelle; Afro Américain; Voix - Marginalisation